2015
DOI: 10.3775/jie.94.170
|View full text |Cite
|
Sign up to set email alerts
|

Study of Demand for CO<sub>2</sub>-free Hydrogen in Japan and the World

Abstract: 世界及び日本における CO 2 フリー水素の導入量の検討 石本祐樹,黒沢厚志,笹倉正晴,坂田 興Evaluation of global hydrogen demand in electricity, stationary and transportation sectors has been conducted under the assumption that CO 2-free hydrogen is produced in seven regions by using a global and long-term intertemporal optimization model, GRAPE. CO2-free hydrogen was assumed to be transported to other regions. Applied CO 2 constraint is 50% reduction for all regions and 80% reduction for developed regions in 2050 from the 1990 level. It has been found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The prospective demand for hydrogen was recently explored [21] to establish a trading link between Patagonia and Japan (Figure 2). While the 2017 Ishimoto reference does not seem to contain the reported data, an earlier paper by the same author [22] indicated that initial demand would be due to stationary fuel cells for combined heat and power (CHP), with transport becoming significant after 2030 and power generation from about 2045.…”
Section: Forecasts Of Demand Growth For Hydrogen In Japanmentioning
confidence: 99%
“…The prospective demand for hydrogen was recently explored [21] to establish a trading link between Patagonia and Japan (Figure 2). While the 2017 Ishimoto reference does not seem to contain the reported data, an earlier paper by the same author [22] indicated that initial demand would be due to stationary fuel cells for combined heat and power (CHP), with transport becoming significant after 2030 and power generation from about 2045.…”
Section: Forecasts Of Demand Growth For Hydrogen In Japanmentioning
confidence: 99%